Monitoring microservices and containerized applications : deployment, configuration, and best practices for Prometheus and Alert Manager - Sabharwal, Navin (APress, 2020)
Discover the methodologies and best practices for getting started with container services monitoring using Prometheus, AppDynamics, and Dynatrace. The book begins with the basics of working with the containerization and microservices architecture while establishing the need for monitoring and management technologies. You'll go through hands-on deployment, configuration, and best practices for Prometheus. Next, you'll delve deeper into monitoring of container ecosystems for availability, performance, and logs, and then cover the reporting capabilities of Prometheus. Further, you'll move on to advanced topics of extending Prometheus including how to develop new use cases and scenarios. You'll then use enterprise tools such as AppDynamics and Wavefront to discover deeper application monitoring best practices. You'll conclude with fully automated deployment of the monitoring and management platforms integrated with the container ecosystem using infrastructure-as -code tools such as Jenkins, Ansible and Terraform. The book provides sample code and best practices for you to look at container monitoring from a holistic viewpoint. This book is a good starting point for developers, architects, and administrators who want to learn about monitoring and management of cloud native and microservices containerized applications. What You Will Learn Examine the fundamentals of container monitoring Get an overview of the architecture for Prometheus and Alert Manager Enable Prometheus monitoring for containers Monitor containers using Wavefront Use the guidelines on container monitoring with enterprise solutions AppDynamics and Wavefront Who This Book Is For Software developers, system administrators, and DevOps engineers working for enterprise customers who want to use monitoring solutions for their container ecosystems.